A Narrative Inquiry Study on Language Learning Through Pop-Up Book - Fais Wahidatul Arifatin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This is a narrative inquiry research that focuses on students perceptions and experiences in language learning using a pop-up book. The aim of this study is to know the influence of pop-up book in learning language through students perception. The use of media in learning is considered very important so that researcher focused on language learning by using realia media in the form of pop-up books. Narrative inquiry research is a form of qualitative research in which researcher obtains data from documentation and student interviews. This research was conducted at MTs Muhammadiyah 13 Solokuro, at the 7th grade level with a total of 9 students. The study took place from March to May 2022. The results of this study indicate that students have a good perception of language learning using pop-up and of course they have new experiences with the methods applied in the learning. There have been many studies on the development and application of a method in learning, while this time the researcher choses to look for something different by looking at the stories, perceptions and experiences of students. Penelitian ini adalah penelitian inquiri naratif yang berfokus pada persepsi dan pengalaman siswa dalam pembelajaran bahasa dengan menggunakan pop-up book. Tujuan dari pada dilakukannya penelitian ini untuk mengetahui seberapa berpengaruh media pop-up book dari persepsi siswa. Penggunaan media dalam pembelajaran dirasa sangat penting sehingga peneliti berfokus pada pembelajaran bahasa dengan menggunakan media realia berbentuk pop-up book. Penelitian inquiri naratif ini adalah bentuk penelitian kualitatif yang mana peneliti mendapatkan data dari dokumentasi dan juga interview siswa. Penelitian ini dilaksanakan di MTs Muhammadiyah 13 Solokuro, pada jenjang kelas 7 yang berjumlah 9 siswa. Penelitian berlangsung dari bulan Maret sampai Mei tahun 2022. Hasil dari penelitian ini menunjukkan bahwa siswa memiliki persepsi yang baik terkait pembelajaran bahasa menggunakan pop-up dan tentu mereka memiliki pengalaman yang baru dengan metode yang diterapkan dalam pembelajaran tersebut. Sudah banyak dijumpai penelitian tentang pengembangan dan penerapan sebuah metode dalam pembelajaran, sedangkan kali ini peneliti memilih mencari hal yang berbeda dengan melihat dari cerita, persepsi, serta pengalaman siswa.